Customer loyalty to newly opened cafés and restaurants in Malaysia. Issue 5 (20th October 2017) - Moorthy, Krishna; En Chee, Lim; Chuan Yi, Ooi; Soo Ying, Ooi; Yee Woen, Ooi; Mun Wei, Tan
ABSTRACT: An extended review of the literature indicates that there is an insufficient number of past studies which test the SERVQUAL model (tangibles, reliability, responsiveness, assurance, empathy) in the food and beverage industry. Therefore, this research attempts to provide new insight into the impact of service quality on customer loyalty in the food and beverage industry. The purpose of the research is to determine the impact of service quality and price fairness on customer loyalty in the food and beverage industry in Penang, Malaysia. This article surveyed the customers of newly opened cafés and restaurants in Penang, Malaysia, by using a structured questionnaire. The research revealed that service quality (tangibles, reliability, assurance, and empathy) and price fairness have a positive relationship with customer loyalty. However, responsiveness had no relationship with customer loyalty. This article includes an additional independent variable, price fairness, to investigate customer loyalty.